Tata Kelola Bencana dan Bicara Belanja: Sinkronisasi Anggaran,Respons Publik, dan Keuangan Negara di Provinsi Lampung - Risma Pitriani Nuryana; M Reza Andrea Putra (Jurnal Ragam Pengabdian, 2026)
Disaster governance is a strategic issue in public administration and public finance, particularly in disaster-prone regions such as Lampung Province, Indonesia. Public expenditure at both national and subnational levels playsa crucial role in supporting disaster prevention, mitigation, emergency response, and post-disaster rehabilitation and reconstruction. However, the magnitude of budget allocation does not necessarily guarantee effective disaster management if it is not supported by sound governance, optimal budget synchronization between central and local governments, andpositive public response. The phenomenon of “talking about spending” reflects increasing public concern regarding transparency, accountability, and the proper use of publicfunds in disaster management. This studyaims to analyze disaster governance in Lampung Province from the perspectives of budget synchronization, public response, and its implications for state finance.Theresearchemploysaqualitativeapproachusingliteraturereview and policy analysis methods. Secondary data are derived from regulatory documents, central and local government financial reports, disaster management reports in Lampung, and relevant academic publications. The data are analyzed thematically to assess the alignment between disaster expenditure policies and the principles of good governance. The findings indicate that disaster-related public spending in Lampung Province continues to face challenges, particularly budget misalignment between central and local governments as well as gaps between planning and implementation stages. These issues contribute to delays in budget realization, inefficiencies in spending, and negative public perceptions. Public response is influenced not only by the size of the budget but also by transparency, accountability, and clarity of information regarding fund utilization. This study addresses a research gap by integrating disaster governance, public expenditure, and public response into a single analytical framework, offering policy implications for strengthening governance and ensuring the sustainability of public finance.